Association of polymorphism TP53 Arg72Pro with radon-induced lung cancer in the Kazakh population - O. Bulgakova; A. Kussainova; A. Kakabayev; А. Kausbekova; R. Bersimbaev (Вавиловский журнал генетики и селекции, 2019)
Lung cancer is a problem of great concern and one of the commonest cancer diseases worldwide and in the Republic of Kazakhstan in particular. Radon exposure is classified as the second most important cause of lung cancer. According to the experts, the contribution of natural sources to the average annual radiation dose of the Kazakh population currently stands at 80 %, including 50 % from radon. However, the effect of radon on human health in the Republic of Kazakhstan is almost unknown. The tumor suppressor gene TP53 is a key mediator of the DNA damage response cascade following cell exposure to ionizing radiation. The common polymorphism TP53 Arg72Pro (rs1042522) is a risk factor for lung cancer in the Asian population, but until now no genetic association studies have been done in the Kazakh population. No information on the synergistic carcinogenic effect of radon exposure and polymorphism TP53 Arg72Pro (rs1042522) is available either. This paper presents the results of the study of association between alteration in the TP53 gene and radon-induced lung cancer risk in the Kazakh population. Genetic association was assessed in a case-control study including 44 radon-exposed patients with lung cancer, 41 patients with lung cancer without radon exposure and 42 age/sex-matched healthy controls. We found that polymorphism TP53 Arg72Pro (rs1042522) was associated with lung cancer risk in the Kazakh population (OR = 6.95, 95 % CI = 2.41–20.05). Individuals with the Arg72Pro genotype also showed a significantly higher risk of radon-induced lung cancer (OR = 8.6, 95 % CI = 2.6–28.59).